Orapuhism: A scholarly philosophy for advancing oral and public health in underserved contexts - V. E. Adamu; NIF Eneojo (Orapuh, Inc., 2024)
Orapuhism, advocated by the founders of Orapuh, is a groundbreaking philosophy aimed at revolutionising oral and public health practices. This article aims to introduce Orapuhism, a novel scholarly philosophy and movement within oral and public health disciplines, to the broader academic and healthcare community. By elucidating its core tenets and implications for practice, this article seeks to stimulate dialogue, foster collaboration, and catalyse positive change in the field of oral and public health. Grounded in the principles of astute scholarship, professional proficiency, and open science, Orapuhism seeks to address healthcare disparities in underserved populations. This article explores the core tenets of Orapuhism as operationalised by the founders of Orapuh and encourages stakeholders to embrace this philosophy to foster positive change in healthcare delivery.